Konflik Norma Penolakan Euthanasia di Indonesia - Endang Prihatin; Ferry Anggriawan (Bhirawa Law Journal, 2023)
Problems in the Human Rights Law which only regulate the right to life and not the right to die. If interpreted broadly, the logic is that if the right to live exists, then the right to die must also exist. If the state legalizes forced deprivation of life by law, then the government should also regulate the legalization of death by its own will in the law. This study aims to examine how the basic considerations of judges in rejecting the Application for Injection of Death or Euthanasia in the Decision of the Banda Aceh District Court are viewed from the perspective of human rights and how the rejection of the Application for Injection of Death or Euthanasia in the Decision of the Banda Aceh District Court is viewed from the perspective of the values of justice . The method used in this study is normative juridical with the following results; The rejection of the application for lethal injection or euthanasia in the Berlin Silalahi case for researchers is a form of injustice and violates the purpose of making the law itself. Whereas euthanasia can be considered as a way to uphold the 'Right to live' by respecting the 'Right to die' with dignity. Furthermore, the application of the practice of euthanasia in Indonesia is actually possible to implement and can bring human rights supremacy in Indonesia closer. The supremacy of human rights here is interpreted to cover human rights as a whole which previously had not been included in positive law so that they could be contained in positive law in Indonesia.